The Impact of the Problem-Based Learning Model with an Open-Ended Approach on the Creative Thinking Skills of 10th Grade Students in Quadratic Function Education - Siahaan, Bertua Marisi Gabryella; Tamba, Ester Maesya; Simbolon, Masri Endayanti; Enjelika, Tri Nova; Simangunsong, Ingrid (AR-RUMMAN: Journal of Education and Learning Evaluation, 2025)
This study aims to evaluate the effect of integrating the Problem-Based Learning (PBL) model with an open-ended approach on the creative thinking skills of 10th-grade students in mathematics, specifically in the topic of Quadratic Functions. The research was conducted at Cahaya Medan Private High School, involving six 10th-grade classes. Two classes were selected as the sample: Class X-2, which participated in the experimental group and received instruction through the PBL model with an open-ended approach, and Class X-3, the control group, which followed traditional teaching methods. Each group consisted of 34 students. A quasi-experimental design was employed, incorporating pretest and posttest evaluations, along with five validated open-ended questions to assess the outcomes. Data analysis was performed using a t-test. The experimental group achieved an average posttest score of 84.94, while the control group scored 77.09. The t-test results showed that the PBL model, when combined with the open-ended approach, significantly improved the students' creative thinking abilities in learning Quadratic Functions.